Forecasting Monthly Red Chili Prices in South Sulawesi Using Prophet Model with Time Series Cross-Validation - Nur Ikhwana; Agung Triutomo; Annisa Syalsabila; Lalu Ramzy Rahmanda (PT ARRUS Intelektual Indonesia, 2026)
This study examines monthly red chili price movements in South Sulawesi using the Prophet forecasting model. Daily price data from the National Strategic Food Price Information Center (PIHPS) covering January 2020 to May 2026 were aggregated into 77 monthly observations. Missing values were handled using linear interpolation and Last Observation Carried Forward (LOCF) before modeling. The Prophet model using for forecasting and time series cross-validation was used as a validation method. The model performance was evaluated by Root Mean Square Error (RMSE), Mean Absolute Error (MAE) and Mean Absolute Percentage Error (MAPE). The results indicate that the model produced an average RMSE = 11,024.68 IDR/kg, MAE = 9,139.04 IDR/kg and MAPE = 23.92%, suggests an acceptable forecasting performance for a highly volatile agricultural commodity. Results pattern demonstrate an annual seasonality on red chili prices, usually lowest price occurs in September and highest one in March of next year. The 12 months projections also foresee a maximum price of 72,597 IDR/kg in March 2027. These results show that the Prophet model can capture trend and seasonality, especially in predicting red chili prices of South Sulawesi.